Innovation For Strengthening Food Independence Using Information Technology - Firza Prima Aditiawan; Teguh Soedarto; Hamidah Hendrarini (Prosiding International conference on Information Technology and Business (ICITB), 2019)
Food independence is the ability of the state and nation to produce diverse foods from within the country that can guarantee the fulfillment of sufficient food needs to the individual levelby utilizing the potential of natural resources, human, social, economic, and local wisdom with dignity. National food security is a strategic issue for Indonesia, various government policies have been carried out to overcome the problem of food availability, one of which is through the implementation of Industry 4.0 in the agricultural sector, farmers can use information technology to find out various information about agriculture, good crop cultivation to the way overcome and overcome various types of plant problems. In addition to farmers, information technology can also be used by agricultural extension workers to provide technical guidance and share information about agriculture without having to go directly to the field, it can increase the empowerment of farmers through preparing agricultural information that is timely and relevant to support the decision making process of farming so that it can increase the productivity of independence and food security.Keywords : Farmers, food security, information technology